2020
DOI: 10.3390/brainsci10060361
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Based Biomarkers Predictive of Metformin Target Engagement in Fragile X Syndrome

Abstract: Recent advances in neurobiology have provided several molecular entrees for targeted treatments for Fragile X syndrome (FXS). However, the efficacy of these treatments has been demonstrated mainly in animal models and has not been consistently predictive of targeted drugs’ response in the preponderance of human clinical trials. Because of the heterogeneity of FXS at various levels, including the molecular level, phenotypic manifestation, and drug response, it is critically important to identify biomarkers that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…They identified several candidates, of which 3 were also shown to be deregulated in the plasma of FXS individuals 35 . A subsequent study validated 2 of those previously identified candidates (along with MMP9) during a clinical trial, showing that their modulation is correlated with treatment efficacy, thus establishing the relevance of the nascent proteome of mice brain to screen for FXS biomarkers 16 . Our present report supports the use of the nascent proteome for biomarker discovery using ex vivo native cells from FX individuals.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…They identified several candidates, of which 3 were also shown to be deregulated in the plasma of FXS individuals 35 . A subsequent study validated 2 of those previously identified candidates (along with MMP9) during a clinical trial, showing that their modulation is correlated with treatment efficacy, thus establishing the relevance of the nascent proteome of mice brain to screen for FXS biomarkers 16 . Our present report supports the use of the nascent proteome for biomarker discovery using ex vivo native cells from FX individuals.…”
Section: Discussionmentioning
confidence: 83%
“…From those, only a handful have been tested in clinical contexts 11 17 . Interestingly, it has been shown that the circulating level of MMP9 (Matrix Metalloproteinase 9), Ras, Hk1 (Hexokinase 1), APP (amyloid-β precursor protein) and ERK (Extracellular Regulated Kinase) phosphorylation in blood platelets can be modulated following specific treatment, thus corroborating their potential use as objective outcome measures for FXS clinical trials 11 , 12 , 14 , 16 . However, clinicians still have no prognostic tools at their disposal, meaning that the announcement of a FX diagnosis is accompanied by a great deal of uncertainty regarding the severity of the comorbidities presented by the affected individual.…”
Section: Introductionmentioning
confidence: 89%
“…The disruption in expression abundance of these proteins was normalized and associated with significant self-reported improvement in clinical phenotypes (CGI-I in addition to body mass index) in a subset of participants with FXS. These preliminary findings suggest that these proteins are of strong molecular relevance to the FXS pathology that could make them useful molecular biomarkers for FXS and targeted treatments [153].…”
Section: Metforminmentioning
confidence: 83%
“…54 Trials in mice and humans have suggested improvements in some symptoms of Fragile X, but results of a double blind, controlled trial in humans are not yet available. 54,55 The antibiotic minocycline has also been shown to reduce MMP9 levels, with improvement in behaviour observed in FXS mice and early human trials. 7 Assessing treatment efficacy of targeted treatments in patients with FXS has been challenging, and this will be true for most genetic forms of intellectual disability.…”
Section: Mendelian Disorders Of Chromatin Machinery -Influencers Of G...mentioning
confidence: 99%
“…In Fragile X mice, metformin has been shown to correct the upregulation of the mGluR/mTORC1‐ERK pathway and the overexpression of matrix metalloproteinase 9 (MMP9), thereby slowing the degradation of proteins that are important for synaptic function 54 . Trials in mice and humans have suggested improvements in some symptoms of Fragile X, but results of a double blind, controlled trial in humans are not yet available 54,55 . The antibiotic minocycline has also been shown to reduce MMP9 levels, with improvement in behaviour observed in FXS mice and early human trials 7 …”
Section: Fragile X Syndrome – Potentially Treatable With Targeted Inh...mentioning
confidence: 99%